2007
DOI: 10.2166/wh.2007.018
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas detection and their toxins from drinking water from reservoirs and drinking fountains

Abstract: Aeromonads are inhabitants of aquatic ecosystems and are described as being involved in intestinal disturbances and other infections. A total of 200 drinking water samples from domestic and public reservoirs and drinking fountains located in Sã o Paulo (Brazil), were analyzed for the presence of Aeromonas. Samples were concentrated by membrane filtration and enriched in APW. ADA medium was used for Aeromonas isolation and colonies were confirmed by biochemical characterization. Strains isolated were tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Aeromonas has been isolated from clinical samples as the sole pathogen, where it was inferred to be the cause of diarrhoea in the studied patients (Hofer et al 2006). Previous studies have shown that Aeromonas strains can carry virulence determinants responsible for infection in humans (Kingombe et al 1999;Sen & Rodgers 2004;Razzolini et al 2008). veronii, Aeromonas schubertii and Aeromonas trota have also been isolated from clinical samples (Ormen et al 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Aeromonas has been isolated from clinical samples as the sole pathogen, where it was inferred to be the cause of diarrhoea in the studied patients (Hofer et al 2006). Previous studies have shown that Aeromonas strains can carry virulence determinants responsible for infection in humans (Kingombe et al 1999;Sen & Rodgers 2004;Razzolini et al 2008). veronii, Aeromonas schubertii and Aeromonas trota have also been isolated from clinical samples (Ormen et al 2003).…”
Section: Introductionmentioning
confidence: 90%
“…hydrophila has also been found in drinking water in (19). These results highlight the pathogenic potential of…”
Section: Study Areamentioning
confidence: 54%
“…Thus, some authors consider that these organisms should be a sanitary quality indicator (7,19,21,24). Moreover, Aeromonas hydrophila is listed in the first and second Contaminant Candidate List (CCL1 and CCL2) by the US Environmental Protection Agency -USEPA (26), linking these organisms to public health adverse outcomes.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations